The Cordyceps militaris-Derived Polysaccharide CM1 Alleviates Atherosclerosis in LDLR(-/-) Mice by Improving Hyperlipidemia - Yin, Fan; Lin, Ping; Yu, Wen-Qian; Shen, Nuo; Li, Yuan; Guo, Shou-Dong (Frontiers in Molecular Biosciences, 2021)
Atherosclerotic cardiovascular disease has a high mortality worldwide. Our lab previously purified a polysaccharide designated as CM1 with (1→4)-β-D-Glcp and (1→2)-α-D-Manp glycosyls as the backbone. In this study, we investigated the anti-atherosclerosis effect of CM1 and the underlying mechanisms of action in a low-density lipoprotein receptor knockout (LDLR(-/-)) mouse model. It was found that CM1 significantly decreased the formation of atherosclerotic plaques. Mechanistically, CM1 enhanced plasma level of apolipoprotein A-I and decreased the plasma levels of triglyceride, apolipoprotein B, and total cholesterol. In the absence of LDLR, CM1 elevated the expression of very low-density lipoprotein receptor for liver uptake of plasma apolipoprotein B-containing particles and reduced hepatic triglyceride synthesis by inhibiting sterol regulatory element binding protein 1c. CM1 improved lipids excretion by increasing the liver X receptor α/ATP-binding cassette G5 pathway in small intestine. CM1 reduced lipogenesis and lipolysis by inhibiting peroxisome proliferator-activated receptor γ and adipose triglyceride lipase in epididymal fat. Furthermore, CM1 improved lipid profile in C57BL/6J mice. Collectively, CM1 can modulate lipid metabolism by multiple pathways, contributing to reduced plasma lipid level and formation of atherosclerotic plaques in LDLR(-/-) mice. This molecule could be explored as a potential compound for prevention and treatment of hyperlipidemia and atherosclerosis.